PAI Teacher Strategy in Improving Learning Effectiveness in Limited Face-to-Face Learning - Radino, Radino; Permatasari, Lia Fatika Yiyi (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – The purpose of this study was to find out PAI and Budi Pekerti Teachers' Strategies in preparing the planning, implementation, methods, and media used as well as evaluating PAI and Budi Pekerti learning to develop the effectiveness of learning in limited face-to-face learning at SMK N 1 Depok. Design/methods/approaches –This research is descriptive qualitative. It involved 3 research subjects, Islamic Religious Education and Moral Education subject teachers for class X, with 20 informants from class X TB students. The data were collected through interviews, observation, and documentation. Data validation technique was done with triangulation technique. Data analysis techniques with data reduction (data selection), data display (data presentation), and conclusion drawing/verification (drawing conclusions). Findings – The results of the study show that: The PAI and Budi Pekerti teacher's strategy in developing the effectiveness of learning in limited face-to-face learning at SMK N 1 Depok is quite effective, PAI and Budi Pekerti teachers prepare learning by the following steps i.e, 1) Making lesson plans based on the syllabus, 2) Preparing material 3) Preparing simple learning media. The teacher's strategy for PAI and Budi Pekerti in carrying out learning to develop learning effectiveness is to carry out learning by paying attention to learning time, the teacher's role as a motivator. Applying appropriate learning methods and providing simple media, PAI Teacher Strategies and PAI and Budi Pekerti characteristics in evaluating learning to develop limited face-to-face learning at SMK N 1 Depok with daily assessments, mid test, and final test. Research implications/limitations – This research has implications for the teacher's strategy in limited face-to-face learning to increase learning effectiveness. Originality/value – This study provides a real picture of the limited face-to-face learning implementation of PAI.